Composite material, method for preparing the same, electrode and battery
Patent Information
- Application Number
- CN202511090274.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-04
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2045-08-04
AI Technical Summary
Graphite produces particles of varying sizes during production, resulting in poor performance and difficulty in achieving tight bonding, thus affecting its application performance.
By performing a two-step oxidation treatment on pulverized materials with different particle sizes, connecting specific functional groups, and then calcining them in an inert atmosphere, followed by mixing, mechanical fusion, isostatic pressing, and graphitization, conductive carbon bridges and an outer protective carbon layer are constructed, achieving tight particle bonding and high conductivity.
It improves the tap density and conductivity of composite materials, enhances the fast-charging and cycle performance of batteries, and achieves 100% utilization of fine powder, thus possessing commercial value.
Smart Images

Figure CN120964791B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of new energy technology, and in particular to a composite material and its preparation method, electrode and battery. Background Technology
[0002] Graphite is an allotrope of carbon, possessing low hardness, stable chemical properties, and resistance to acids, alkalis, and other reagents. It also exhibits high temperature resistance, corrosion resistance, thermal shock resistance, radiation resistance, high strength, good toughness, and high electrical and thermal conductivity. As a result, it is widely used in metallurgy, machinery, electronics, military industry, national defense, aerospace, and other fields.
[0003] In related technologies, graphite produces particles of different sizes during the production process. These particles are difficult to fit together tightly, resulting in poor graphite performance, which needs further improvement. Summary of the Invention
[0004] In view of this, this application provides a composite material, a method for preparing the same, an electrode, and a battery.
[0005] The embodiments of this application are implemented as follows: Firstly, the embodiments of this application provide a method for preparing a composite material, comprising the following steps: The raw material coke is provided, and after being crushed, a first crushed material and a second crushed material are obtained. The average particle size of the first crushed material is larger than the average particle size of the second crushed material. The first pulverized material is subjected to a first oxidation treatment and a second oxidation treatment in sequence, wherein the temperature of the second oxidation treatment is higher than the temperature of the first oxidation treatment, to obtain a first modified pulverized material; The first modified pulverized material and the second pulverized material are mixed and then subjected to first fusion, first carbonization and graphitization treatments in sequence to obtain a composite material.
[0006] Optionally, in some embodiments of this application, the temperature of the first oxidation treatment is 180°C to 240°C, and the time of the first oxidation treatment is 5 min to 8 min; After the first oxidation treatment, a first group is attached to the first pulverized material. The first group includes one or more of hydroxyl, carboxyl, and carbonyl groups. The first group and the first pulverized material are connected by chemical bonds. The temperature of the second oxidation treatment is 300℃~400℃, and the time of the second oxidation treatment is 2min~5min; After the second oxidation treatment, a second group is attached to the first pulverized material. The second group includes one or more of ether bonds, cyclic carbonyl groups, and cyclic ester groups. The second group and the first pulverized material are connected by chemical bonds. After the first oxidation treatment and before the second oxidation treatment, the process further includes: performing a first calcination treatment in an inert atmosphere; the temperature of the first calcination treatment is 240℃~300℃, and the time of the first calcination treatment is 20min~40min; After the second oxidation treatment and before obtaining the first modified pulverized material, the process further includes: performing a second calcination treatment in an inert atmosphere; the temperature of the second calcination treatment is 300℃~400℃, and the time of the second calcination treatment is 10min~20min.
[0007] Optionally, in some embodiments of this application, the raw material coke includes one or more of oil-based coke and coal-based coke; the oil-based coke is selected from one or more of petroleum coke and oil-based needle coke, and the coal-based coke is selected from one or more of coal-based needle coke and pitch coke; The average particle size of the first pulverized material is 6μm~14μm; The average particle size of the second pulverized material is 1μm~5μm; The mass ratio of the first pulverized material to the second pulverized material is (60~90):(10~40).
[0008] Optionally, in some embodiments of this application, the first fusion is stirring, and the first fusion includes a first fusion a and a first fusion b performed sequentially, wherein the stirring frequency of the first fusion b is greater than the stirring frequency of the first fusion a; wherein, The stirring frequency of the first fusion a is 20Hz~30Hz, and the time of the first fusion a is 3h~6h; The stirring frequency of the first fusion b is 30Hz~40Hz, and the stirring time of the first fusion b is 1h~3h; The first fusion process further includes: adding one or more of a first binder and a conductive agent; the first binder is selected from one or more of a polymer and an asphalt-based cementitious material, wherein the polymer is selected from one or more of styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylic acid, polyacrylamide, polyvinyl alcohol, sodium alginate, and polyurethane, and the asphalt-based cementitious material is selected from one or more of emulsified asphalt and tar; the mass ratio of the first modified pulverized material to the second pulverized material and to the first binder is 100:(4~20); the conductive agent is selected from a carbon conductive agent, wherein the carbon conductive agent is selected from one or more of conductive carbon black, artificial graphite, single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene; the mass ratio of the first binder to the conductive agent is 100:(1~1.5). After the first fusion, a first fusion product is obtained, and the average particle size of the first fusion product is 8μm~18μm.
[0009] Optionally, in some embodiments of this application, the temperature of the first carbonization is 800°C to 900°C, and the time of the first carbonization is 4h to 8h; The graphitization temperature is 3000℃~3200℃, and the graphitization time is 70h~90h.
[0010] Optionally, in some embodiments of this application, after the first carbonization and before the graphitization, the process further includes: performing isostatic pressing; the isostatic pressing process includes cold isostatic pressing; the cold isostatic pressing process includes a first cold isostatic pressing process, a second cold isostatic pressing process, and a third cold isostatic pressing process performed sequentially, wherein the pressure of the second cold isostatic pressing process is greater than the pressure of the first cold isostatic pressing process, and the pressure of the third cold isostatic pressing process is greater than the pressure of the second cold isostatic pressing process; wherein... The pressurization rate to the pressure of the first cold isostatic pressing treatment is greater than 0 MPa / min and less than or equal to 10 MPa / min; the pressure of the first cold isostatic pressing treatment is greater than 0 MPa and less than 100 MPa; the holding time of the first cold isostatic pressing treatment is 1 min to 5 min. The pressurization rate to the pressure of the second cold isostatic pressing treatment is 10MPa / min to 20MPa / min, the pressure of the second cold isostatic pressing treatment is 100MPa to 150MPa, and the holding time of the second cold isostatic pressing treatment is 3min to 10min. The pressurization rate to the pressure of the third cold isostatic pressing treatment is 20MPa / min~30MPa / min, the pressure of the third cold isostatic pressing treatment is 150MPa~300MPa, and the holding time of the third cold isostatic pressing treatment is 30min~40min. After the isostatic pressing treatment, an isostatic pressing product is obtained, and the average particle size of the isostatic pressing product is 8μm~16μm.
[0011] Optionally, in some embodiments of this application, after graphitization, a graphitized product is obtained, and the preparation method further includes: performing a second fusion on the graphitized product, wherein the second fusion is stirring; wherein, The stirring frequency for the second fusion is 30Hz~40Hz, and the fusion time is 3h~6h; The second fusion process further includes: adding a second binder; the second binder is selected from one or more of polymers and asphalt-based cementitious materials, wherein the polymer is selected from one or more of styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylic acid, polyacrylamide, polyvinyl alcohol, sodium alginate, and polyurethane, and the asphalt-based cementitious material is selected from one or more of emulsified asphalt and tar; the mass ratio of the graphitized product to the second binder is 100:(6~10). After the second fusion, a second carbonization is also performed; the temperature of the second carbonization is 1100℃~1200℃, and the time of the second carbonization is 6h~8h.
[0012] Secondly, embodiments of this application also provide a composite material prepared by the above-described preparation method.
[0013] Optionally, in some embodiments of this application, the composite material includes at least one composite particle, the composite particle including a first particle and a second particle, wherein the average particle size of the first particle is larger than the average particle size of the second particle, and the second particle is partially embedded in the first particle; wherein, The material of the first particle includes a first graphite material, and the material of the second particle includes a second graphite material; The average particle size of the first particle is 6 μm to 14 μm; the average particle size of the second particle is 1 μm to 5 μm. In the composite particles, the mass ratio of the first particle to the second particle is (60~90):(10~40).
[0014] Optionally, in some embodiments of this application, the composite particles further include a first binder, wherein the first binder connects the first particles and the second particles; the composite material includes a plurality of the composite particles, and the composite material further includes a second binder, wherein the second binder connects the plurality of the composite particles; wherein... The first adhesive and the second adhesive are each independently selected from one or more of polymers and asphalt-based cementitious materials. The polymer is selected from one or more of styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylic acid, polyacrylamide, polyvinyl alcohol, sodium alginate, and polyurethane. The asphalt-based cementitious material is selected from one or more of emulsified asphalt and tar. The first adhesive and the second adhesive may be made of the same or different materials; The mass ratio of the first particle to the second particle and the mass ratio of the first particle to the first adhesive is 100:(4~20). The mass ratio of the composite particles to the second binder is 100:(6~10).
[0015] Optionally, in some embodiments of this application, the composite particles further include a conductive agent; wherein, The conductive agent is selected from carbon conductive agents, which are selected from one or more of conductive carbon black, artificial graphite, single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene. The mass ratio of the first adhesive to the conductive agent is 100:(1~1.5); The conductive agent is located at the junction of the first particle and the second particle.
[0016] Optionally, in some embodiments of this application, the average particle size of the composite material is 12 μm to 16 μm; The tap density of the composite material is 1.2 g / cm³. 3 ~1.4g / cm 3 ; The specific surface area of the composite material is 1.1 m². 2 / g~1.4m 2 / g.
[0017] Thirdly, embodiments of this application also provide an electrode, the material of which includes the composite material prepared by the above-described preparation method, or includes the above-described composite material.
[0018] Fourthly, embodiments of this application also provide a battery, the battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the material of the negative electrode comprises a composite material prepared by the above-described preparation method, or comprises the above-described composite material, or the negative electrode comprises the above-described electrode.
[0019] The preparation method provided in this application involves a two-step oxidation treatment of the finished pulverized material after crushing and shaping, followed by mixing with recycled fine powder. This two-step oxidation process increases defect sites, promoting the embedding and tight bonding of the recycled fine powder, and introduces stable second groups to ensure uniform spreading of the binder, achieving further tight bonding and improving the high compaction density and high vibration density of the composite material. Using a binder and conductive agent, plastic bridges are constructed through mechanical fusion and medium-temperature carbonization. Secondary particle reconstruction is achieved through isostatic pressing and crushing / shaping processes, resulting in dense and highly conductive particles, which are then subjected to graphitization treatment. To address the surface microcracks or fissures resulting from graphitization, mechanical fusion carbonization is employed to construct carbon layers, ensuring optimal cycle performance. Through the synergistic processing of mechanical fusion and isostatic pressing techniques, conductive carbon bridges and an outer protective carbon layer are efficiently constructed. Furthermore, with the synergistic effect of a suitable amount of fine powder, the composite material prepared in this application exhibits high tap density and compaction density, as well as a low specific surface area. When applied to batteries, it demonstrates excellent fast-charging performance, adequate cycle performance, and high-temperature performance, while also possessing a very high yield advantage (100% utilization of fine powder), making it highly commercially valuable. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 This is a flowchart of a method for preparing a composite material provided in an embodiment of this application. Detailed Implementation
[0022] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application. Furthermore, it should be understood that the specific embodiments described herein are only for illustration and explanation of this application and are not intended to limit this application.
[0023] In this application, unless otherwise stated, directional terms such as "upper" and "lower" generally refer to the upper and lower positions of the device in its actual use or operating state, specifically the orientation shown in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. Furthermore, in the description of this application, the term "comprising" means "including but not limited to". The terms first, second, third, etc., are used merely as illustrative purposes and do not impose numerical requirements or establish a numerical order.
[0024] In this application, "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural.
[0025] In this application, "at least one" means one or more, and "more than one" means two or more. "One or more", "at least one of the following", or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0026] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the referred range.
[0027] During graphite production, fine powder with small particle size is generated. Due to its poor morphology and irregular particle surface, this fine powder results in lower tap density and higher specific surface area, negatively impacting graphite performance. When used in batteries, small-particle-size graphite reduces the initial cycle efficiency and initial discharge capacity, leading to performance and processing defects. Effective recycling of this fine powder is hindered and requires further improvement.
[0028] The technical solution of this application is as follows: Firstly, please refer to Figure 1 This application also provides a method for preparing a composite material, comprising the following steps: Step S11: Provide raw coke, crush it to obtain a first crushed material and a second crushed material, wherein the average particle size of the first crushed material is greater than the average particle size of the second crushed material. Step S12: The first pulverized material is subjected to a first oxidation treatment and a second oxidation treatment in sequence. The temperature of the second oxidation treatment is higher than that of the first oxidation treatment to obtain the first modified pulverized material. Step S13: Mix the first modified pulverized material and the second pulverized material, and sequentially perform the first fusion, first carbonization, and graphitization treatments to obtain the composite material.
[0029] In step S11: In some embodiments, the raw material coke includes one or more of oil-based coke and coal-based coke. Further, the oil-based coke is selected from one or more of petroleum coke and oil-based needle coke, and the coal-based coke is selected from one or more of coal-based needle coke and pitch coke.
[0030] It should be noted that the pulverization can be achieved by conventional technical means in the field, such as mechanical grinding, ultrafine grinding, roller grinding, ring roller grinding, air jet grinding, etc. after being fed into a pulverizer.
[0031] In some embodiments, after the raw material coke is crushed, it further includes classification. It should be noted that in process, crushed materials of suitable particle size are often screened for subsequent operations through classification. The remaining fine powder after screening results in waste and reduces production capacity. In this solution, the first crushed material is the finished crushed material with a suitable particle size after screening, while the second crushed material is the remaining fine powder. This solution modifies the finished crushed material and then mixes it with all the recovered fine powder. By modifying the finished crushed material, the embedding of fine powder is facilitated, improving the performance of the fine powder, and ultimately enhancing the performance of the composite material.
[0032] In some embodiments, the average particle size of the first pulverized material is 6μm to 14μm, for example, it can be 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm or any range between two of the above values. The average particle size of the first pulverized material is suitable, and its processing performance is good.
[0033] In some embodiments, the average particle size of the second pulverized material is 1 μm to 5 μm, for example, it can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or any range between two of the above values. The average particle size of the second pulverized material is relatively small and is often removed as a byproduct during production. This solution fully recycles and reuses it, which can improve production capacity and yield.
[0034] In some embodiments, the mass ratio of the first pulverized material to the second pulverized material is (60~90):(10~40), for example, it can be 60:40, 70:30, 80:20, or 90:10. It should be noted that the mass ratio of the first pulverized material to the second pulverized material can be determined according to the actual output after pulverization and grading.
[0035] In step S12: It should be noted that the oxidation treatment is a process of introducing oxygen and heating to oxidize the first pulverized material.
[0036] In some embodiments, the temperature of the first oxidation treatment is 180°C to 240°C, for example, it can be 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C or any two of the above values; the time of the first oxidation treatment is 5 min to 8 min, for example, it can be 5 min, 6 min, 7 min, 8 min or any two of the above values.
[0037] The temperature of the second oxidation treatment is 300℃~400℃, for example, it can be 300℃, 320℃, 350℃, 380℃, 400℃ or any two of the above values; the time of the second oxidation treatment is 2min~5min, for example, it can be 2min, 3min, 4min, 5min or any two of the above values.
[0038] Under the oxidation treatment conditions provided in this application, the oxidation temperature and time are appropriate. If the oxidation temperature is too high or the time is too long, it will damage the original structure and properties of the pulverized material, increase expansion, reduce the degree of graphitization, and make it easy to burn. If the oxidation temperature is too low or the time is too short, it will not be able to achieve the oxidation etching effect.
[0039] In some embodiments, after the first oxidation treatment, a first group is attached to the first pulverized material. The first group includes one or more of hydroxyl, carboxyl, and carbonyl groups. The first group and the first pulverized material are connected by chemical bonds.
[0040] In some embodiments, after the second oxidation treatment, a second group is attached to the first pulverized material. The second group includes one or more of ether bonds, cyclic carbonyl groups, and cyclic ester groups. The second group and the first pulverized material are connected by chemical bonds.
[0041] It is understood that the ether bond refers to The functional group (with carbon atoms attached to both sides of oxygen) refers to a carbonyl group ( The functional groups on both sides of the cyclic ester group refer to the ester group ( Functional groups that form a ring on both sides.
[0042] It should be noted that the ether bond, the cyclic carbonyl group, and the cyclic ester group are part of the second group, such as an diethyl ether group (…). When ), the diethyl ether group contains an ether bond. Groups containing a cyclic carbonyl group can be quinone groups (…). , , , (etc.) A cyclic ester group represents a lactone group; groups containing a cyclic ester group can be... , , wait.
[0043] It should also be noted that the second group can be obtained by further oxidation of a portion of the first group.
[0044] It should be further explained that the first oxidation treatment can generate abundant, hydrophilic, and highly reactive primary functional groups on the surface of the first pulverized material (especially at edges and defects). During the second oxidation treatment, some of these unstable groups can be decomposed and converted into more stable secondary functional groups, and preliminary dehydrogenation crosslinking may occur, while maintaining the original structure and properties of the pulverized material. The second oxidation treatment can solve the problem of unstable groups and regenerate more stable groups without damaging the original structure and properties of the pulverized material. If only the first oxidation treatment is performed, unstable groups will be easily removed during subsequent heat treatment, resulting in a loss of the oxidation etching effect and even worsening the granulation performance.
[0045] After the first and second oxidation treatments, the surface defect sites on the first modified pulverized material can be increased, thereby allowing the second pulverized material to be tightly embedded. Furthermore, by introducing a stable second group, the bonding force between the subsequent first binder and the first modified pulverized material can be enhanced.
[0046] In some embodiments, after the first oxidation treatment and before the second oxidation treatment, a first calcination treatment is performed in an inert atmosphere.
[0047] In some embodiments, after the second oxidation treatment and before obtaining the first modified pulverized material, a second calcination treatment is further performed in an inert atmosphere.
[0048] Furthermore, the temperature of the first calcination treatment is higher than the temperature of the first oxidation treatment, but lower than the temperature of the second oxidation treatment. This buffers the first pulverized material containing the second group, preventing structural changes in the first pulverized material caused by rapid temperature variations.
[0049] Furthermore, the temperature of the first calcination treatment is 240℃~300℃, for example, it can be 240℃, 250℃, 260℃, 270℃, 280℃, 290℃, 300℃ or any two of the above values; the time of the first calcination treatment is 20min~40min, for example, it can be 20min, 25min, 30min, 35min, 40min or any two of the above values.
[0050] The temperature of the second calcination treatment can be the same as the temperature of the second oxidation treatment. The temperature of the second calcination treatment is 300℃~400℃, for example, 300℃, 320℃, 350℃, 380℃, 400℃ or any two of the above values; the time of the second calcination treatment is 10min~20min, for example, 10min, 12min, 15min, 18min, 20min or any two of the above values.
[0051] In some embodiments, the inert gas in the inert atmosphere may be one or more of argon and nitrogen.
[0052] Thus, under the conditions of the above-mentioned calcination treatment, the surface structure and properties formed after each oxidation can be stabilized.
[0053] In step S13: It should be noted that the first fusion refers to feeding the first modified pulverized material and the second pulverized material into a fusion machine, so that the second pulverized material embeds into the first modified pulverized material. The first modified pulverized material introduces stable groups and also enhances defect sites, making it easier for the second pulverized material to partially embed into the surface layer of the first modified pulverized material.
[0054] In some embodiments, the first fusion is stirring. The first fusion includes a first fusion a and a first fusion b performed sequentially, wherein the stirring frequency of the first fusion b is greater than the stirring frequency of the first fusion a.
[0055] Furthermore, the stirring frequency of the first fusion a is 20Hz~30Hz, for example, it can be 20Hz, 22Hz, 25Hz, 28Hz, 30Hz or any two of the above values, and the time of the first fusion a is 3h~6h, for example, it can be 3h, 4h, 5h, 6h or any two of the above values.
[0056] The stirring frequency of the first fusion b is 30Hz~40Hz, for example, it can be 30Hz, 32Hz, 35Hz, 38Hz, 30Hz or any two of the above values, and the time of the first fusion b is 1h~3h, for example, it can be 1h, 2h, 3h or any two of the above values.
[0057] Thus, under the aforementioned first fusion conditions, first fusion a facilitates the initial fusion of the first modified pulverized material and the second pulverized material, determining the initial embedding sites. First fusion b has a faster frequency, which facilitates the further embedding of the second pulverized material into the first modified pulverized material, achieving a tight connection.
[0058] In some embodiments, the first fusion process further includes adding one or more of a first binder and a conductive agent. It should be noted that the first binder and the conductive agent can be added together, and the conductive agent and the first binder are located together at the junction of the first particle and the second particle.
[0059] In some embodiments, the first adhesive is selected from one or more of polymers and bitumen-based binders, wherein the polymer is selected from one or more of styrene-butadiene rubber (SBR, polystyrene-butadiene copolymer), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate, and polyurethane (WPU), and the bitumen-based binder is selected from one or more of emulsified bitumen and tar.
[0060] In some embodiments, the conductive agent is selected from carbon conductive agents. More specifically, the carbon conductive agent is selected from one or more of SP (Super P, conductive carbon black), KS-6 (artificial graphite), single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene.
[0061] In some embodiments, the mass ratio of the first modified pulverized material to the second pulverized material and to the first binder is 100:(4~20), for example, it can be 100:4, 100:5, 100:8, 100:10, 100:12, 100:15, 100:18, 100:20, or any range between two of the above ratios. Within the range of said mass ratio, it is beneficial for the first binder to tightly connect the first modified pulverized material and the second pulverized material, enhancing their interlocking degree.
[0062] In some embodiments, the mass ratio of the first binder to the conductive agent is 100:(1~1.5), for example, it can be 100:1, 100:1.1, 100:1.2, 100:1.3, 100:1.4, 100:1.5, or any range between two of the above ratios. Within the range of the mass ratio, the conductive agent can enhance the conductivity and other properties of the composite material.
[0063] It should be noted that the first binder and the conductive agent can be mixed and added together in the form of a spray. It should also be noted that after the first oxidation treatment and the second oxidation treatment, a second group is introduced onto the surface of the first modified pulverized material, which can improve the polarity and wettability of the first modified pulverized material, making it easier for the first binder to spread evenly on the surface of the first modified pulverized material, and resulting in a more uniform contact and connection between the first modified pulverized material and the second pulverized material, thereby obtaining a denser composite material.
[0064] In some embodiments, after the first fusion, a first fusion product is obtained, and the average particle size of the first fusion product is 8μm to 18μm, for example, it can be 8μm, 10μm, 12μm, 15μm, 18μm or any two of the above values.
[0065] In some embodiments, the temperature of the first carbonization is 800℃~900℃, for example, it can be 800℃, 820℃, 840℃, 860℃, 880℃, 900℃ or any range between two of the above values; the time of the first carbonization is 4h~8h, for example, it can be 4h, 5h, 6h, 7h, 8h or any range between two of the above values. Thus, under the conditions of the first carbonization, it is beneficial for the first modified pulverized material and the second pulverized material to undergo preliminary carbonization, so that the components of the raw coke are converted into carbides.
[0066] It should be noted that the first carbonization can be carried out in a carbonization furnace (microwave carbonization furnace, roller kiln / tunnel kiln / rotary kiln / pusher kiln, etc.).
[0067] In some embodiments, after the first carbonization and before the graphitization, the process further includes: performing isostatic pressing.
[0068] Furthermore, the isostatic pressing treatment includes cold isostatic pressing.
[0069] Furthermore, the cold isostatic pressing process includes a first cold isostatic pressing process, a second cold isostatic pressing process, and a third cold isostatic pressing process performed sequentially, wherein the pressure of the second cold isostatic pressing process is greater than the pressure of the first cold isostatic pressing process, and the pressure of the third cold isostatic pressing process is greater than the pressure of the second cold isostatic pressing process.
[0070] In some embodiments, the pressurization rate to the pressure of the first cold isostatic pressing treatment is greater than 0 MPa / min and less than or equal to 10 MPa / min, for example, it can be 1 MPa / min, 2 MPa / min, 5 MPa / min, 8 MPa / min, 10 MPa / min or any range between two of the above values; the pressure of the first cold isostatic pressing treatment is greater than 0 MPa and less than 100 MPa, for example, it can be 10 MPa, 20 MPa, 50 MPa, 80 MPa, 100 MPa or any range between two of the above values; the holding time of the first cold isostatic pressing treatment is 1 min to 5 min, for example, it can be 1 min, 2 min, 3 min, 4 min, 5 min or any range between two of the above values.
[0071] In some embodiments, the pressurization rate to the pressure of the second cold isostatic pressing treatment is 10 MPa / min to 20 MPa / min, for example, it can be 10 MPa / min, 12 MPa / min, 15 MPa / min, 18 MPa / min, 20 MPa / min or any two of the above values; the pressure of the second cold isostatic pressing treatment is 100 MPa to 150 MPa, for example, it can be 100 MPa, 110 MPa, 120 MPa, 130 MPa, 140 MPa, 150 MPa or any two of the above values; the holding time of the second cold isostatic pressing treatment is 3 min to 10 min, for example, it can be 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min or any two of the above values.
[0072] In some embodiments, the pressurization rate to the pressure of the third cold isostatic pressing treatment is 20 MPa / min to 30 MPa / min, for example, it can be 20 MPa / min, 22 MPa / min, 25 MPa / min, 28 MPa / min, 30 MPa / min or any two of the above values; the pressure of the third cold isostatic pressing treatment is 150 MPa to 300 MPa, for example, it can be 150 MPa, 200 MPa, 250 MPa, 280 MPa, 300 MPa or any two of the above values; the holding time of the third cold isostatic pressing treatment is 30 min to 40 min, for example, it can be 30 min, 32 min, 35 min, 38 min, 40 min or any two of the above values.
[0073] Thus, under the aforementioned cold isostatic pressing conditions, the second pulverized material in the first carbonized product can be compacted and densified, facilitating secondary morphology reconstruction and yielding a product with uniform particle size and good sphericity.
[0074] In some embodiments, after the isostatic pressing treatment, an isostatic pressing product is obtained, and the average particle size of the isostatic pressing product is 8μm to 16μm, for example, it can be 8μm, 10μm, 12μm, 15μm, 16μm or any two of the above values.
[0075] In some embodiments, the graphitization temperature is 3000℃~3200℃, for example, it can be 3000℃, 3050℃, 3100℃, 3150℃, 3200℃, or any range between two of the above values; the graphitization time is 70h~90h, for example, it can be 70h, 75h, 80h, 85h, 90h, or any range between two of the above values. Thus, under the aforementioned graphitization conditions, it is beneficial for the raw materials to be fully graphitized, ensuring the formation of the graphite matrix.
[0076] In some embodiments, after graphitization, a graphitized product is obtained, and the preparation method further includes: performing a second fusion on the graphitized product, wherein the second fusion is stirring.
[0077] It should be noted that after graphitization, the resulting material is a composite material in which the second pulverized material is partially embedded in the first modified pulverized material. The second fusion involves feeding the composite pulverized material into a fusion machine to tightly connect the composite pulverized materials together.
[0078] In some embodiments, the stirring frequency for the second fusion is 30Hz to 40Hz, for example, it can be 30Hz, 32Hz, 35Hz, 38Hz, 30Hz, or any range between two of the above values, and the second fusion time is 3h to 6h, for example, it can be 3h, 4h, 5h, 6h, or any range between two of the above values. Under the conditions of the second fusion, it is beneficial to have a tight connection between the composite particles.
[0079] In some embodiments, the second fusion process further includes adding a second adhesive.
[0080] In some embodiments, the second adhesive is selected from one or more polymers and bitumen-based binders, wherein the polymer is selected from one or more of styrene-butadiene rubber (SBR, polystyrene-butadiene copolymer), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate, and polyurethane (WPU), and the bitumen-based binder is selected from one or more of emulsified bitumen and tar.
[0081] It is understood that the first adhesive and the second adhesive may be made of the same or different materials.
[0082] In some embodiments, the mass ratio of the graphitized product to the second binder is 100:(6~10), for example, it can be 100:6, 100:7, 100:8, 100:9, 100:10, or any range between two of the above ratios. Within the range of the mass ratio, it is beneficial for the second binder to tightly connect the composite particles, thereby improving the structural stability of the composite material.
[0083] In some embodiments, after the second fusion, a second carbonization is further performed. Further, the temperature of the second carbonization is 1100℃~1200℃, for example, 1100℃, 1120℃, 1150℃, 1180℃, 1200℃, or any range between two of the above values; the time of the second carbonization is 6h~8h, for example, 6h, 7h, 8h, or any range between two of the above values. Thus, under the conditions of the second carbonization, it is beneficial for the graphitized product to undergo sufficient further carbonization, resulting in a composite material with high conductivity and stable structure.
[0084] It should be noted that the second carbonization process is carried out in an inert atmosphere.
[0085] The preparation method provided in this application involves a two-step oxidation treatment of the finished pulverized material after crushing and shaping, followed by mixing with recycled fine powder. This two-step oxidation process increases defect sites, promoting the embedding and tight bonding of the recycled fine powder, and introduces stable second groups to ensure uniform spreading of the binder, achieving further tight bonding and improving the high compaction density and high vibration density of the composite material. Using a binder and conductive agent, plastic bridges are constructed through mechanical fusion and medium-temperature carbonization. Secondary particle reconstruction is achieved through isostatic pressing and crushing / shaping processes, resulting in dense and highly conductive particles, which are then subjected to graphitization treatment. To address the surface microcracks or fissures resulting from graphitization, mechanical fusion carbonization is employed to construct carbon layers, ensuring optimal cycle performance. Through the synergistic processing of mechanical fusion and isostatic pressing techniques, conductive carbon bridges and an outer protective carbon layer are efficiently constructed. Furthermore, with the synergistic effect of a suitable amount of fine powder, the composite material prepared in this application exhibits high tap density and compaction density, as well as a low specific surface area. When applied to batteries, it demonstrates excellent fast-charging performance, adequate cycle performance, and high-temperature performance, while also possessing a very high yield advantage (100% utilization of fine powder), making it highly commercially valuable.
[0086] Secondly, embodiments of this application provide a composite material prepared by the above-described preparation method.
[0087] In some embodiments, the composite material includes at least one composite particle, the composite particle comprising a first particle and a second particle, wherein the average particle size of the first particle is larger than the average particle size of the second particle, and the second particle is partially embedded in the first particle. The first particle is made of a first graphite material, and the second particle is made of a second graphite material.
[0088] It should be noted that the second particle is partially embedded in the first particle, meaning that the surface of the first particle has pits and the second particle fills the pits. The first particle and the second particle interlock with each other through the surface irregularities or edges, restricting their displacement. Through geometric interlocking, a stable mechanical structure is formed, thereby enhancing the overall strength and deformation resistance of the composite particle.
[0089] The composite material provided in this application includes composite particles of different sizes, namely, first particles and second particles. The second particles can be fine powder recovered during the preparation process, which can be effectively and rationally utilized to improve production capacity and yield. The second particles are tightly embedded in the surface of the first particles to achieve mechanical interlocking between the first and second particles and improve connection stability. The composite material provided in this application can obtain high tap density and low specific surface area, and when applied to batteries, it has excellent fast charging performance, appropriate cycle performance and good high temperature resistance.
[0090] In some embodiments, the average particle size of the first particle is 6 μm to 14 μm, for example, it can be 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or any range between two of the above values. The average particle size of the first particle is suitable, and its processing performance is good.
[0091] In some embodiments, the average particle size of the second particle is 1 μm to 5 μm, for example, it can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or any range between two of the above values. The average particle size of the second particle is relatively small and is often removed as a byproduct during production. This solution fully recycles and reuses it, which can improve production capacity and yield.
[0092] In some embodiments, the mass ratio of the first particle to the second particle in the composite particles is (60~90):(10~40), for example, 60:40, 70:30, 80:20, or 90:10. Within the range of the mass ratio, the first particle and the second particle can synergistically improve the tap density and stability of the composite material.
[0093] In some embodiments, the composite particles further include a first binder.
[0094] Furthermore, in the composite particles, the first binder connects the first particle and the second particle. The first binder facilitates a tighter bond between the first particle and the second particle, increasing the tap density and reducing the specific surface area.
[0095] The material of the first adhesive is as described above and will not be repeated here.
[0096] In some embodiments, the mass ratio of the first particle to the second particle and the mass ratio of the first particle to the first adhesive is 100:(4~20), for example, it can be 100:4, 100:5, 100:8, 100:10, 100:12, 100:15, 100:18, 100:20, or any range between two of the above ratios. Within the range of said mass ratio, it is beneficial for the first adhesive to tightly connect the first particle and the second particle, enhancing their interlocking degree.
[0097] In some embodiments, the composite particles further include a conductive agent.
[0098] The material of the conductive agent is described above and will not be repeated here.
[0099] In some embodiments, the mass ratio of the first binder to the conductive agent is 100:(1~1.5), for example, it can be 100:1, 100:1.1, 100:1.2, 100:1.3, 100:1.4, 100:1.5, or any range between two of the above ratios. Within the range of the mass ratio, the conductive agent can enhance the conductivity of the composite particles and improve the performance of the composite material.
[0100] In some embodiments, the conductive agent is located at the junction of the first particle and the second particle.
[0101] In some embodiments, the composite material comprises a plurality of the composite particles, and the composite material further comprises a second binder that connects the plurality of composite particles. The second binder can connect the plurality of composite particles together to form the composite material.
[0102] The material of the second adhesive is as described above and will not be repeated here.
[0103] In some embodiments, the mass ratio of the composite particles to the second binder is 100:(6~10), for example, it can be 100:6, 100:7, 100:8, 100:9, 100:10, or any range between two of the above ratios. Within the range of the mass ratio, it is beneficial for the second binder to tightly connect the composite particles, thereby improving the structural stability of the composite material.
[0104] In some embodiments, the average particle size of the composite material is 12 μm to 16 μm, for example, it can be 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm, 15 μm, 15.5 μm, 16 μm, or any range between two of the above values. Within this range of average particle size, the application of the composite material is improved.
[0105] In some embodiments, the tap density of the composite material is 1.2 g / cm³. 3 ~1.4g / cm 3 For example, it can be 1.2 g / cm³. 3 1.21 g / cm 3 1.23g / cm 3 1.25g / cm 3 1.27g / cm 3 1.29g / cm 3 1.3g / cm 3 1.33g / cm 3 1.35g / cm 3 1.38g / cm 3 1.4g / cm 3 Or the range between any two of the above values, etc.
[0106] In some embodiments, the specific surface area of the composite material is 1.1 m². 2 / g~1.4m 2 / g, for example, can be 1.1m 2 / g, 1.15m 2 / g, 1.2m 2 / g, 1.25m 2 / g, 1.3m 2 / g, 1.35m 2 / g, 1.4m 2 / g or the range between any two of the above values, etc.
[0107] Thus, within the aforementioned range of tap density and specific surface area, the composite material exhibits good performance when applied to battery electrodes, allowing for the filling of more composite material within the same space and improving conductivity.
[0108] Thirdly, embodiments of this application also provide an electrode, the material of which includes the composite material prepared by the above-described preparation method, or includes the above-described composite material.
[0109] Fourthly, embodiments of this application also provide a battery, the battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the material of the negative electrode comprises a composite material prepared by the above-described preparation method, or comprises the above-described composite material.
[0110] The positive electrode, separator, and electrolyte can be made of conventional materials in this field.
[0111] The present application will be specifically described below through specific embodiments. The following embodiments are only some embodiments of the present application and are not intended to limit the present application.
[0112] Composite Material Example 1 This embodiment of the composite material provides a composite material, and the preparation method of the composite material includes the following steps: Step S21: The raw material coke (petroleum coke) is first dried and coarsely crushed, then mechanically ground in a pulverizer. A classifier is used to obtain a first pulverized material with a particle size D50 of 7.5 μm and a second pulverized material with a particle size D50 of 3.5 μm. The first pulverized material is subjected to a first oxidation treatment at 200℃ for 6 min, followed by calcination at 300℃ in an inert atmosphere for 20 min, and then a second oxidation treatment at 350℃ for 3 min. After the second oxidation treatment, calcination at 350℃ in an inert atmosphere is continued for 10 min, and the material is cooled to room temperature to obtain the first modified pulverized material. The second pulverized material and the first modified pulverized material were uniformly mixed at a mass ratio of 30:70 to obtain a mixed pulverized material. The mixed pulverized material was put into a room temperature mechanical fusion machine, and the first binder polyacrylamide (mass ratio of mixed pulverized material to first binder of 100:11) and the conductive agent KS-6 (mass ratio of first binder to conductive agent of 100:1.2) were added in the form of spray. The fusion machine frequency was 25Hz and maintained for 4 hours. Then the frequency was adjusted to 35Hz and stabilized for 1.5 hours to obtain the first fusion product. Step S22: The first fusion product is fed into a rotary kiln and subjected to first carbonization at 700℃ for 6 hours to obtain the first carbonized product. The first carbonized product is then fed into a cold isostatic pressing furnace for cold isostatic pressing treatment. The pressure is increased from 10 MPa / min to 80 MPa and held for 1.5 min, increased from 20 MPa / min to 120 MPa and held for 5 min, and increased from 30 MPa / min to 280 MPa and held for 32 min. The pressure is then slowly released from the furnace, and the cold isostatic pressing product is crushed and shaped, and then fed into an Atchison furnace for graphitization at 3000℃ for 79 hours. After cooling, the graphitized product is obtained. Step S23: The graphitized product and the second binder tar are mixed at a mass ratio of 100:7 and then mechanically fused at a fusion frequency of 35Hz for 4.5 hours. The mixture is then sent to a roller kiln for second carbonization under an inert atmosphere throughout the process. The carbonization temperature is 1150℃ and the holding time is 7 hours. The mixture is then allowed to cool naturally to room temperature, undergo micro-depolymerization and shaping, and is sieved and demagnetized to obtain the composite material.
[0113] Composite Material Example 2 This composite material embodiment is basically the same as composite material embodiment 1, except that the temperature of the first oxidation treatment in step S21 of this composite material embodiment is 240°C.
[0114] Composite Material Example 3 This composite material embodiment is basically the same as composite material embodiment 1, except that the temperature of the first oxidation treatment in step S21 of this composite material embodiment is 180°C.
[0115] Composite Material Example 4 This composite material embodiment is basically the same as composite material embodiment 1, except that the temperature of the second oxidation treatment in step S21 of this composite material embodiment is 400°C.
[0116] Composite Material Example 5 This composite material embodiment is basically the same as composite material embodiment 1, except that the temperature of the second oxidation treatment in step S21 of this composite material embodiment is 300°C.
[0117] Composite Material Example 6 This composite material embodiment is basically the same as the composite material embodiment 1, except that the first binder in step S21 of this embodiment is replaced with emulsified asphalt.
[0118] Composite Material Example 7 This composite material embodiment is basically the same as composite material embodiment 1, except that in step S21 of this composite material embodiment, the mass ratio of the mixed crushed material to the first binder is 100:20.
[0119] Composite Material Example 8 This composite material embodiment is basically the same as composite material embodiment 1, except that in step S21 of this composite material embodiment, the mass ratio of the mixed crushed material to the first binder is 100:4.
[0120] Composite Material Example 9 This composite material embodiment is basically the same as the composite material embodiment 1, except that the second binder in step S23 of this embodiment is replaced with sodium alginate.
[0121] Composite Material Example 10 This composite material embodiment is basically the same as composite material embodiment 1, except that in step S23 of this composite material embodiment, the mass ratio of graphitized product to second binder is 100:10.
[0122] Composite Material Example 11 This composite material embodiment is basically the same as composite material embodiment 1, except that in step S23 of this composite material embodiment, the mass ratio of graphitized product to second binder is 100:6.
[0123] Composite Material Example 12 This composite material embodiment is basically the same as composite material embodiment 1, except that in step S21 of this composite material embodiment, the mass ratio of the second pulverized material to the first modified pulverized material is 40:60.
[0124] Composite Material Example 13 This composite material embodiment is basically the same as composite material embodiment 1, except that in step S21 of this composite material embodiment, the mass ratio of the second pulverized material to the first modified pulverized material is 10:90.
[0125] Composite Material Example 14 This composite material embodiment is basically the same as composite material embodiment 1, except that in step S21 of this composite material embodiment, the raw material coke is replaced with coal-based needle coke, and the particle size D50 of the first pulverized material is 8.5 μm.
[0126] Composite Material Example 15 This composite material embodiment is basically the same as composite material embodiment 1, except that in step S21 of this composite material embodiment, the first oxidation treatment is 8 min and the second oxidation treatment is 5 min.
[0127] Composite Material Example 16 This composite material embodiment is basically the same as composite material embodiment 1, except that in step S22 of this composite material embodiment, the pressure of the third cold isostatic pressing is 230MPa.
[0128] Composite Material Example 17 This composite material embodiment is basically the same as composite material embodiment 1, except that in step S22 of this composite material embodiment, the holding time for the three cold isostatic pressings is 3 min, 7 min, and 38 min, respectively.
[0129] Composite Material Comparative Example 1 The comparative example of this composite material is basically the same as that of Example 1 of the composite material, except that the first oxidation treatment and the second oxidation treatment in step S21 were not performed in this comparative example of the composite material.
[0130] Composite Material Comparative Example 2 The comparative example of this composite material is basically the same as that of Example 1 of the composite material. The only difference is that the second pulverized material was not recovered in this comparative example of the composite material, and the first oxidation treatment and the second oxidation treatment were not performed. Only the first pulverized material was subjected to subsequent operations.
[0131] Composite Material Comparative Example 3 The comparative example of this composite material is basically the same as that of Example 1 of the composite material. The only difference is that the first pulverized material was not used in the comparative example of this composite material, and the first oxidation treatment and the second oxidation treatment were not performed. Only the second pulverized material was used for subsequent operations.
[0132] Composite Material Comparative Example 4 This composite material comparative example is basically the same as composite material comparative example 3, the only difference being that cold isostatic pressing was not performed in this composite material comparative example.
[0133] Composite material comparative example 5 The comparative example of this composite material is basically the same as that of Example 1 of the composite material, except that only the first oxidation treatment was performed in the comparative example of this composite material, and the second oxidation treatment was not performed.
[0134] Composite Material Comparative Example 6 The comparative example of this composite material is basically the same as that of Example 1 of the composite material, except that the first oxidation treatment and the second oxidation treatment were not performed in this comparative example of the composite material, but an oxidation treatment of 700°C for 8 minutes was performed.
[0135] The particle size D00 and particle size D50, tap density, specific surface area and powder compaction density of the composite materials in Examples 1-17 and Comparative Examples 1-6 were tested. The test results are shown in Table 1.
[0136] Among them, particle size was tested using a Malvern Panaco Zetasizer Ultra dynamic scattering particle size analyzer; tap density was tested using a Canta tap density instrument; specific surface area (BET) was tested using a Canta specific surface area analyzer; and powder compaction density (5T) was tested using a force testing universal tester.
[0137] Table 1
[0138] From Table 1, we can obtain: As can be seen from the composite material examples 1-17 and the composite material comparative examples 1-6, this scheme solves the problem of fine powder recycling and increasing production capacity by recycling fine powder with smaller particle size. Furthermore, by performing two oxidation modifications on the first pulverized material, it promotes the close interlocking and cohesive connection of the first pulverized material and the second pulverized material (fine powder), thereby increasing the tap density and reducing the specific surface area, which is beneficial to the application of composite materials.
[0139] Battery Example 1 This battery embodiment provides a button cell battery and a fully enclosed battery.
[0140] The preparation method of the coin cell includes the following steps: the composite material of the composite material example 1 is mixed with conductive agent (SP), binder (CMC, sodium carboxymethyl cellulose) and binder (SBR, styrene-butadiene rubber) at a ratio of 95:1.5:1.5:2, coated on copper foil, vacuum dried and used as the negative electrode, lithium metal as the counter electrode, the electrolyte is a mixture of ethylene carbonate (EC) and dimethyl carbonate (DMC) of 1MLiPP6 at a mass ratio of 1:1, the separator is a PE / PPPE composite membrane, and the coin cell is assembled.
[0141] The preparation method of the fully enclosed battery includes the following steps: the positive electrode formula is lithium iron phosphate:PVDF:SP at 96%:2%:2% and the negative electrode formula is the composite material of Example 1:CMC:SBR:SP at 95.5%:1.5%:2%:1%; through slurry preparation, coating, rolling, slitting, winding, assembly and formation, a soft-pack battery is obtained.
[0142] Battery Examples 2-17 Battery Examples 2-17 are basically the same as Battery Example 1, except that the composite material of Composite Material Example 1 is replaced with the composite material of Composite Material Examples 2-17 in Battery Examples 2-17.
[0143] Battery Comparison 1~6 Battery Comparative Examples 1 to 6 are basically the same as Battery Example 1, except that the composite material of Composite Material Example 1 is replaced with the composite material of Composite Material Comparative Examples 1 to 6 in Battery Comparative Examples 1 to 6.
[0144] The charge-discharge performance and cycle performance of the coin cells in Examples 1-17 and Comparative Examples 1-6 were tested: the charging voltage was limited to 0.005V~2V, the first discharge efficiency and the first discharge capacity were recorded, and the cycle capacity was tested again after 200 cycles to calculate the cycle capacity retention rate; in addition, the charge transfer internal resistance (Rct) was tested by electrochemical impedance spectroscopy, and the compaction density of the negative electrode was tested. The test results are shown in Table 2.
[0145] Table 2
[0146] From Table 2, we can obtain: As can be seen from battery examples 1-17 and battery comparative examples 1-6, the embodiments of this application controlled suitable conditions and steps, and the composite material prepared was applied to the battery, which significantly improved the first discharge efficiency and first discharge capacity of the battery; after 200 cycles, it still maintained a high capacity retention rate; the negative electrode sheet had a high compaction density, which allowed more active material to be packed in a unit volume, meeting the requirements of small size and high capacity, and the charge transfer internal resistance was small, which was conducive to improving charge transport and conduction, thus improving the performance of the battery.
[0147] Rate performance tests were conducted on the pouch cells of Battery Example 1 and Comparative Examples 1-6: Charge-discharge cycles were performed at 1C, 3C, and 6C current densities, with the charging voltage limited to 3.5-4V. Rate performance tests were conducted at different rates (50 cycles at a single rate), and the rate capacity retention rate was the percentage of remaining capacity to initial capacity under the specified rate. Furthermore, high and low temperature storage performance tests were performed on the pouch cells: They were placed under low temperature (-20℃) and high temperature (60℃) conditions, respectively, and the first charge-discharge cycle was performed after 14 days. The percentage ratio of the remaining capacity to the initial capacity was recorded as the high and low temperature capacity retention rate. The test results are shown in Table 3.
[0148] Table 3
[0149] From Table 3, we can obtain: As can be seen from Battery Example 1 and Battery Comparative Examples 1 to 6, after cycling at various different rates, the soft-pack battery examples still maintain a high capacity retention rate, especially after 6C rate cycling, the performance is significantly improved; under high temperature and low temperature storage conditions, they also maintain a high capacity retention rate, improve temperature resistance performance, and have good storage properties.
[0150] The technical solutions provided by the embodiments of this application have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of this application. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.
Claims
1. A method for preparing a composite material, characterized in that, Includes the following steps: The raw material coke is provided, and after being crushed, a first crushed material and a second crushed material are obtained. The average particle size of the first crushed material is larger than the average particle size of the second crushed material. The first pulverized material is subjected to a first oxidation treatment and a second oxidation treatment in sequence, wherein the temperature of the second oxidation treatment is higher than the temperature of the first oxidation treatment, to obtain a first modified pulverized material; The first modified pulverized material and the second pulverized material are mixed and then subjected to a first fusion, a first carbonization, and a graphitization process in sequence to obtain a composite material. The temperature of the first oxidation treatment is 180℃~240℃; the temperature of the second oxidation treatment is 300℃~400℃.
2. The preparation method according to claim 1, characterized in that, The first oxidation treatment lasts for 5 to 8 minutes. After the first oxidation treatment, a first group is attached to the first pulverized material. The first group includes one or more of hydroxyl, carboxyl, and carbonyl groups. The first group and the first pulverized material are connected by chemical bonds. The second oxidation treatment lasts for 2 to 5 minutes. After the second oxidation treatment, a second group is attached to the first pulverized material. The second group includes one or more of ether bonds, cyclic carbonyl groups, and cyclic ester groups. The second group and the first pulverized material are connected by chemical bonds. After the first oxidation treatment and before the second oxidation treatment, the process further includes: performing a first calcination treatment in an inert atmosphere; the temperature of the first calcination treatment is 240℃~300℃, and the time of the first calcination treatment is 20min~40min; After the second oxidation treatment and before obtaining the first modified pulverized material, the process further includes: performing a second calcination treatment in an inert atmosphere; the temperature of the second calcination treatment is 300℃~400℃, and the time of the second calcination treatment is 10min~20min.
3. The preparation method according to claim 1, characterized in that, The raw material coke includes one or more of oil-based coke and coal-based coke; the oil-based coke is selected from one or more of petroleum coke and oil-based needle coke, and the coal-based coke is selected from one or more of coal-based needle coke and pitch coke; The average particle size of the first pulverized material is 6μm~14μm; The average particle size of the second pulverized material is 1μm~5μm; The mass ratio of the first pulverized material to the second pulverized material is (60~90):(10~40).
4. The preparation method according to claim 1, characterized in that, The first fusion is stirring, and the first fusion includes a first fusion a and a first fusion b performed sequentially, wherein the stirring frequency of the first fusion b is greater than the stirring frequency of the first fusion a; wherein, The stirring frequency of the first fusion a is 20Hz~30Hz, and the time of the first fusion a is 3h~6h; The stirring frequency of the first fusion b is 30Hz~40Hz, and the stirring time of the first fusion b is 1h~3h; The first fusion process further includes: adding one or more of a first binder and a conductive agent; the first binder is selected from one or more of a polymer and an asphalt-based cementitious material, wherein the polymer is selected from one or more of styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylic acid, polyacrylamide, polyvinyl alcohol, sodium alginate, and polyurethane, and the asphalt-based cementitious material is selected from one or more of emulsified asphalt and tar; the mass ratio of the first modified pulverized material to the second pulverized material and to the first binder is 100:(4~20); the conductive agent is selected from a carbon conductive agent, wherein the carbon conductive agent is selected from one or more of conductive carbon black, artificial graphite, single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene; the mass ratio of the first binder to the conductive agent is 100:(1~1.5). After the first fusion, a first fusion product is obtained, and the average particle size of the first fusion product is 8μm~18μm.
5. The preparation method according to claim 1, characterized in that, The temperature of the first carbonization is 800℃~900℃, and the time of the first carbonization is 4h~8h; The graphitization temperature is 3000℃~3200℃, and the graphitization time is 70h~90h.
6. The preparation method according to claim 1, characterized in that, After the first carbonization and before the graphitization, the process further includes: performing isostatic pressing; the isostatic pressing process includes cold isostatic pressing; the cold isostatic pressing process includes a first cold isostatic pressing process, a second cold isostatic pressing process, and a third cold isostatic pressing process performed sequentially, wherein the pressure of the second cold isostatic pressing process is greater than the pressure of the first cold isostatic pressing process, and the pressure of the third cold isostatic pressing process is greater than the pressure of the second cold isostatic pressing process; wherein... The pressurization rate to the pressure of the first cold isostatic pressing treatment is greater than 0 MPa / min and less than or equal to 10 MPa / min; the pressure of the first cold isostatic pressing treatment is greater than 0 MPa and less than 100 MPa; the holding time of the first cold isostatic pressing treatment is 1 min to 5 min. The pressurization rate to the pressure of the second cold isostatic pressing treatment is 10MPa / min to 20MPa / min, the pressure of the second cold isostatic pressing treatment is 100MPa to 150MPa, and the holding time of the second cold isostatic pressing treatment is 3min to 10min. The pressurization rate to the pressure of the third cold isostatic pressing treatment is 20MPa / min~30MPa / min, the pressure of the third cold isostatic pressing treatment is 150MPa~300MPa, and the holding time of the third cold isostatic pressing treatment is 30min~40min. After the isostatic pressing treatment, an isostatic pressing product is obtained, and the average particle size of the isostatic pressing product is 8μm~16μm.
7. The preparation method according to claim 1, characterized in that, After graphitization, a graphitized product is obtained. The preparation method further includes: performing a second fusion on the graphitized product, wherein the second fusion is stirring; wherein... The stirring frequency for the second fusion is 30Hz~40Hz, and the fusion time is 3h~6h; The second fusion process further includes: adding a second binder; the second binder is selected from one or more of polymers and asphalt-based cementitious materials, wherein the polymer is selected from one or more of styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylic acid, polyacrylamide, polyvinyl alcohol, sodium alginate, and polyurethane, and the asphalt-based cementitious material is selected from one or more of emulsified asphalt and tar; the mass ratio of the graphitized product to the second binder is 100:(6~10). After the second fusion, a second carbonization is also performed; the temperature of the second carbonization is 1100℃~1200℃, and the time of the second carbonization is 6h~8h.
8. A composite material, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 7.
9. The composite material as described in claim 8, characterized in that, The composite material includes at least one composite particle, which comprises a first particle and a second particle. The average particle size of the first particle is larger than the average particle size of the second particle, and the second particle is partially embedded in the first particle. The material of the first particle includes a first graphite material, and the material of the second particle includes a second graphite material; The average particle size of the first particle is 6 μm to 14 μm; the average particle size of the second particle is 1 μm to 5 μm. In the composite particles, the mass ratio of the first particle to the second particle is (60~90):(10~40).
10. The composite material as described in claim 9, characterized in that, The composite particles further include a first binder, wherein the first binder connects the first particles and the second particles; the composite material includes a plurality of the composite particles, and the composite material further includes a second binder, wherein the second binder connects the plurality of composite particles; wherein... The first adhesive and the second adhesive are each independently selected from one or more of polymers and asphalt-based cementitious materials. The polymer is selected from one or more of styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylic acid, polyacrylamide, polyvinyl alcohol, sodium alginate, and polyurethane. The asphalt-based cementitious material is selected from one or more of emulsified asphalt and tar. The first adhesive and the second adhesive may be made of the same or different materials; The mass ratio of the first particle to the second particle and the mass ratio of the first particle to the first adhesive is 100:(4~20). The mass ratio of the composite particles to the second binder is 100:(6~10).
11. The composite material as described in claim 10, characterized in that, The composite particles also include a conductive agent; wherein... The conductive agent is selected from carbon conductive agents, which are selected from one or more of conductive carbon black, artificial graphite, single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene. The mass ratio of the first adhesive to the conductive agent is 100:(1~1.5); The conductive agent is located at the junction of the first particle and the second particle.
12. The composite material as described in claim 8, characterized in that, The average particle size of the composite material is 12μm~16μm; The tap density of the composite material is 1.2 g / cm³. 3 ~1.4g / cm 3 ; The specific surface area of the composite material is 1.1 m². 2 / g~1.4m 2 / g.
13. An electrode, characterized in that, The electrode material includes a composite material prepared by the preparation method according to any one of claims 1 to 7, or a composite material according to any one of claims 8 to 12.
14. A battery, characterized in that, The battery includes a positive electrode, a negative electrode, a separator, and an electrolyte. The material of the negative electrode includes a composite material prepared by the preparation method according to any one of claims 1 to 7, or a composite material according to any one of claims 8 to 12, or the negative electrode includes an electrode according to claim 13.
Citation Information
Patent Citations
Artificial graphite composite negative electrode material for lithium ion battery and preparation method for negative electrode material
CN107369823A
High-rate lithium ion battery artificial graphite negative electrode material and preparation method thereof
CN112573923A
High-compaction-density and high-rate-performance graphite negative electrode material and preparation method thereof
CN114873589A
